Inflammatory markers in pregnancy – identifying drivers in four large cohorts - Gigase, Frederieke A. J.; Suleri, Anna; Isaevska, Elena; Rommel, Anna-Sophie; Boekhorst, Myrthe G. B. M.; Dmitrichenko, Olga; El Marroun, Hanan; Steegers, Eric A. P.; Hillegers, Manon H. J.; Muetzel, Ryan L.; Lieb, Whitney; Cecil, Charlotte A. M.; et al. (Frontiers in Immunology, 2025)
IntroductionAdaptations of the immune system throughout gestation have been proposed as important mechanisms regulating successful pregnancy. Dysregulation of the maternal immune system has been associated with adverse maternal and fetal outcomes. The design and interpretation of human biomarker studies require additional insights in the trajectories and drivers of peripheral immune markers. MethodsThe current study mapped maternal inflammatory markers (C-reactive protein (CRP), interleukin (IL)-1β, IL-6, IL-17A, IL-23, interferon-γ) during pregnancy and investigated the impact of demographic, environmental and genetic drivers on maternal inflammatory marker levels in four multi-ethnic and socio-economically diverse population-based cohorts with more than 12,000 pregnant participants. Additionally, pregnancy inflammatory markers were compared to pre-pregnancy levels. ResultsCytokines showed a high correlation with each other, but not with CRP. Inflammatory marker levels showed high variability between individuals, yet high concordance within an individual over time during and pre-pregnancy. Pre-pregnancy body mass index (BMI) explained ~ 9.6% of the variance in CRP, but less than 1% of the variance in cytokines. The polygenic score of CRP was the best predictor of variance in CRP (14.1%). Gestational age and previously identified inflammation drivers, including tobacco use and parity, explained less than 1% of variance in both cytokines and CRP.DiscussionOur findings corroborate differential underlying regulatory mechanisms of CRP and cytokines and are suggestive of an individual inflammatory marker baseline which is, in part, genetically driven.